Age stereotypes' effects on motor learning in older adults: The impact may not be immediate, but instead delayed. (May 2018) - Chiviacowsky, Suzete; Cardozo, Priscila Lopes; Chalabaev, Aïna
Abstract: Recent research with young adults has demonstrated that stereotype threat can impact not only immediate performance, but also the learning of motor skills. Studies examining this phenomenon on motor learning in other populations, however, are still lacking. The objective of the present study was to investigate whether stereotypes influence motor learning in older adults. Participants (all females; age range: 60–76 years) were divided into three groups. Before practice they were informed that their performance would be compared with the performance of young adults (negative condition), with performance of participants 20 years older (positive condition), or that performance on the task was not influenced by age (control condition). The results of a retention test showed worse learning for participants in the negative group relative to the other groups. The results provide the first evidence that stereotypes can impact motor learning in older adults. Highlights: We investigate the effects of age stereotypes on balance learning in older adults. Participants practice in three stereotype conditions: positive, negative and control. The negative condition performs worse in retention than the other conditions. Age stereotypes can affect motor learning in older adults.